2019
DOI: 10.1155/2019/4359524
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Speed Control of a Spindle Cluster Driven by Hydraulic Motor: Application to Metal Cutting Machines

Abstract: In this article, we present an experimental study on the speed stability of a spindle driven by a hydraulic motor, which is controlled by a proportional valve, through a V-belt transmission. The research includes the dynamic modeling of the transmission cluster and the transmission from the hydraulic motor to the working shaft via V-belt mechanism, together with the establishment of a mathematical model and fuzzy self-tuning PID controller model. In the model, the V-belt is assumed as an elastic module, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A drum (9) is mounted on the shaft of the hydraulic motor, on which a steel cable is wound. The object (13) is attached to the end of the steel cable. The object is attached to the linear guide.…”
Section: Linear Rotary Electro-hydraulic Servo Drive Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…A drum (9) is mounted on the shaft of the hydraulic motor, on which a steel cable is wound. The object (13) is attached to the end of the steel cable. The object is attached to the linear guide.…”
Section: Linear Rotary Electro-hydraulic Servo Drive Unitmentioning
confidence: 99%
“…The authors presented the test stand of a winch with a hydraulic motor and the results of simulation tests. More studies on hydraulic motors can be found in [11][12][13]. In the article [14], the authors presented a crawler robot with four actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Relationship between the tooth number and displacement. We take the example that the form of the solar pitch curve is a high-order ellipse as equation (1). According to the above description, the displacement and unit volume displacement of the non-circular planetary gear hydraulic motor of the less than 1 tooth type can be obtained, as shown in Table 2.…”
Section: Formulaic Processing Of the Hydraulic Motor Displacementmentioning
confidence: 99%
“…Figure 10 shows the relationship between the number of planetary gear teeth and the displacement of the motor and the displacement of the unit volume for the hydraulic motor of less 1 tooth type. V m1 and V 1 are respectively the unit volume displacement and displacement of the hydraulic motor when the solar pitch curve is a high-order elliptic as equation (1). Here, the minimum value of Z 2 is 7 and the maximum value of V m1 is 0.7577/r.…”
Section: Optimization Equation Of the Solar Pitch Curvementioning
confidence: 99%